2001
DOI: 10.2139/ssrn.923370
|View full text |Cite
|
Sign up to set email alerts
|

Currency Orders and Exchange-Rate Dynamics: Explaining the Success of Technical Analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…models, too (see, e.g. Allen and Taylor, 1990;Chang and Osler, 1999;Fiess and MacDonald, 2002;Osler, 2000Osler, , 2003. Further in-depth analyses confirm the earlier finding of a complementary use of technical analysis even for a world where flows matter besides fundamentals and charts.…”
Section: Discussionsupporting
confidence: 67%
“…models, too (see, e.g. Allen and Taylor, 1990;Chang and Osler, 1999;Fiess and MacDonald, 2002;Osler, 2000Osler, , 2003. Further in-depth analyses confirm the earlier finding of a complementary use of technical analysis even for a world where flows matter besides fundamentals and charts.…”
Section: Discussionsupporting
confidence: 67%
“…These predictions have been substantiated for support and resistance levels distributed to customers by major market players (Osler 2000). As outlined in Osler (2003), this highly non-linear behavior follows logically when one combines the influence of order flow on returns with the asymmetric clustering of stop-loss and take-profit orders near round numbers.…”
Section: Order Flow and The Profitability Of Technical Analysismentioning
confidence: 95%
“…Unfortunately, this does not appear to always be the case. Osler (2003) found that stop-loss buy orders are more strongly clustered above than below trigger points with round numbers, and the opposite is true for stop-loss sell orders. This means that estimates of order flow derived from portfolio holdings may be less accurate when the spot rate is the neighborhood a trigger point with round numbers.…”
Section: Further Implicationsmentioning
confidence: 89%